Extra classes and subjective well-being: empirical evidence from Vietnamese children - Ko, I; Xing, J (Young Lives, 2009)
Do children with access to private tutoring feel happier than those without? In answering this question, this paper offers a novel way to understand the potential merit of providing private tutoring for children. Using a unique data set on Vietnamese children from Round 2 of the Young Lives 2006 Survey, this paper explores the link between taking extra classes and a child's subjective well-being, measured by degree of satisfaction regarding their current and future life. Estimation results from Ordinary Least-Square regressions indicate such a link to be positive and significant, which is further confirmed by Ordered Probit regressions aiming to control for the discontinuous nature of the dependent variable. To control for potential endogeneity of households' choice to purchase extra classes, the method of Propensity Score Matching is applied. Results from different versions of nearest-neighbour matching and Kernel matching indicate that children with private tutoring tend to feel happier about their current life, although the long-run effect of taking extra classes on a child's subjective well-being is more sensitive to the matching methods used.